2003
DOI: 10.1097/00002030-200307040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of JC virus-specific CD4 T-cell responses in preventing progressive multifocal leukoencephalopathy

Abstract: JCV-specific CD4 T-cell responses appear to play a critical role in the control of JCV infection, preventing PML development. Such responses can be restored in PML survivors following effective and prolonged antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 32 publications
6
87
0
1
Order By: Relevance
“…A disconcerting issue, however, is the long-term safety of B cell-depleting agents. Fatal progressive multifocal leukoencephalopathy after JC virus reactivation is associated with suppression of T cell-mediated immunity (45,46) and has been reported in five rituximab-treated autoimmune disease patients (including two with SLE) (47), and clinical trials of ocrelizumab, a next-generation version of rituximab, were recently halted because of unacceptable serious and fatal infections.…”
Section: Discussionmentioning
confidence: 99%
“…A disconcerting issue, however, is the long-term safety of B cell-depleting agents. Fatal progressive multifocal leukoencephalopathy after JC virus reactivation is associated with suppression of T cell-mediated immunity (45,46) and has been reported in five rituximab-treated autoimmune disease patients (including two with SLE) (47), and clinical trials of ocrelizumab, a next-generation version of rituximab, were recently halted because of unacceptable serious and fatal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in animal models demonstrated that virus-specific CD4 + T cells are critical for the expansion of virus-specific CD8 + T cells, their differentiation to memory cells, their recruitment to sites of infection, and their secondary expansion during reinfection (1-7), as well as for efficient neutralizing-Ab-mediated virus clearance (8). In humans, the importance of virus-specific CD4 + T cells in control of viral infections has been shown for different viruses such as HIV (9,10), hepatitis C virus (11), and also for JC polyoma virus (JCV) (12). JCV is a ubiquitous virus that infects between 60 and 80% of the population worldwide.…”
Section: Irus-specific Cd4mentioning
confidence: 99%
“…Natalizumab does not affect antibody production. Most adults are seropositive for JC virus, and although the humoral immune response cannot prevent a reactivation of JC virus and the development of PML, we and others have found that the cellular immune response plays a crucial role in the containment of JC virus [20][21][22][23][24] and is mediated by CD8+ cytotoxic T cells. The BK virus, a polyomavirus related to JC virus, may be reactivated in patients with multiple sclerosis who are treated with natalizumab.…”
mentioning
confidence: 78%